2016
DOI: 10.1097/ico.0000000000000950
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of Central Corneal Thickness in Patients With Systemic Sclerosis

Abstract: CCT decreased with time in SSc. However, the slight rates of thinning observed are unlikely to considerably influence applanation tonometry or clinical decision-making over the short to intermediate term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…There are several reports in the literature involving corneal thickness measurements in systemic sclerosis. [19][20][21] Gomes et al found that central corneal thickness decreases over time in systemic sclerosis. 19 In another study, it was reported that corneal thickness in the patients with systemic sclerosis is similar to that in the healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports in the literature involving corneal thickness measurements in systemic sclerosis. [19][20][21] Gomes et al found that central corneal thickness decreases over time in systemic sclerosis. 19 In another study, it was reported that corneal thickness in the patients with systemic sclerosis is similar to that in the healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Gomes et al found that central corneal thickness decreases over time in systemic sclerosis. 19 In another study, it was reported that corneal thickness in the patients with systemic sclerosis is similar to that in the healthy individuals. 20 Nagy et al found that pachymetry and corneal volume were signi cantly lower in the patients with systemic sclerosis than in the healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports in the literature involving corneal thickness measurements in systemic sclerosis. [19][20][21] Gomes et al found that central corneal thickness decreases over time in systemic sclerosis. 19 In another study, it was reported that corneal thickness in the patients with systemic sclerosis is similar to that in the healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Gomes et al found that central corneal thickness decreases over time in systemic sclerosis. 19 In another study, it was reported that corneal thickness in the patients with systemic sclerosis is similar to that in the healthy individuals. 20 Nagy et al found that pachymetry and corneal volume were signi cantly lower in the patients with systemic sclerosis than in the healthy individuals.…”
Section: Discussionmentioning
confidence: 99%